Penyebab Penunggakan Pajak Bumi dan Bangunan dan Upaya Penanggulangan di Kelurahan Fatululi Kecamatan Oebobo Kota Kupang - Grasela Mariana Ballo; Rafael Rape Tupen; Cyrilius Wilton Taran Lamataro (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Rural and Urban Land and Building Tax is one of the main sources of State revenue for development financing. In the implementation of PBB-P2 collection, there are still many people who are not aware of the rights and obligations in paying taxes, this is due to the fact that there is still very low public awareness and knowledge in paying taxes. Public awareness as taxpayers in paying taxes will increase if there is an understanding of taxes in society. This research is an empirical legal research where data is obtained directly from the research location. Two types and sources of data are used, namely: primary data and secondary data. The data collection technique uses interview guidelines and literature/journal studies. The results of this study show that: (1). Taxpayer income in Fatululi Village is still very low in taxpayer awareness, economic conditions and the influence of Covid-19. (2). The government's countermeasures are still lacking in socialization or counseling to the taxpayer community. Suggestions need to be further increased socialization or counseling to the public about understanding paying PBB and need to be emphasized the existing tax sanctions.